Monitoring through T2 Hotelling of cylinder lubrication process of marine diesel engine. (5th January 2017) - Boullosa, David; Larrabe, Juan Luis; Lopez, Alberto; Gomez, Miguel Angel
Highlights: Process monitoring of Marine diesel engine cylinder lubrication. Detection of signals in the process, with a new data entry. Identification of process variables signaling that originated. Abstract: Frequently, it can be complex to identify when a process, has a deviation from its normal working conditions, when the process variables are individually monitored. This paper responds to that need. The cylinder lubrication process, of a 2T marine diesel engine, was monitored throughout multivariate control charts, for specific ship operation conditions; the historical data set in control the optimal working process was made and with a new entry of sample n = 23, observations out of statistical control were detected using Hotelling's T 2 control charts. The variables that generated the signals in the process were identified through the MYT decomposition technique. This technique could complement and not supplement the systems which monitor the independent variables and have a general vision of the behavior of the complete process.